(3QSGdI aj GdYed HGdCSWQdGHs - (3GdeanqVd Hf YeQ Hf GdeaVd GdCHgQj GdSeQbfOj, CKjQ GdOjf,J (B663 (3g` s
(3ChdgG (B:s
(3GdaUd GdChd ai JYQja GdGUWdGMGJ CeG GdUaGFM gi GdUajMI GdJi JMjW HgG MdbI ebSheI s
(3BNQgG (B:s
(3hfCNP eG Hjf GdYdGbJjf ai GdCQV hfVQHg ai GKfi YTQ aeG HdZ agh GQJaGY GdTNU hPdc hgh GdeQGO hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GfXQg eY GdeNWhW Qbe (B169 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3HgG ebGHdIs
(3fSNI fajSI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3Gdadcs